Effect of Elevated Temperature on the Mechanical Properties of Concrete Produced with Finely Ground Pumice and Silica Fume - Demirel, Bahar; Keleştemur, Oğuzhan (My University, 2010)
This study investigated the effect of elevated temperature on the mechanical and physical properties of concrete specimens obtained by substituting cement with finely ground pumice (FGP) at proportions of 5%, 10%, 15% and 20% by weight. To determine the effect of silica fume (SF) additive on the mechanical and physical properties of concrete containing FGP, SF has been added to all series except for the control specimen, which contained 10% cement by weight instead. The specimens were heated in an electric furnace up to 400, 600 and 800 1C and kept at these temperatures for one hour. After the specimens were cooled in the furnace, ultrasonic pulse velocity (UPV), compressive strength and weight loss values were determined. The results demonstrated that adding the mineral admixtures to concrete decreased both unit weight and compressive strength. Additionally, elevating the temperature above 600 1C affected the compressive strength such that the weight loss of concrete was more pronounced for concrete mixtures containing both FGP and SF. These results were also supported by scanning electron microscope (SEM) studies
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Concrete; Elevated temperature; Finely ground pumice; Silica fume; C-S-G gel